Student’s Social Presence and perceive learning toward CCU course in the online classroom. (An Evaluating of Learning Process during Pandemic Coronavirus) - Nirwana, Nirwana; Muhlis, Muhlis (Elite : English and Literature Journal, 2020)
Social distancing policies during the pandemic, have a significant influence on the education system in Indonesia. This condition requires all the education levels to carry out the learning process into an online classroom, although the readiness has not been well prepared. it certainly affects the quality of learning which previously still uses more face to face learning, no exception for English and Literature department at Islamic state university of Makassar. Cross Cultural Understanding as one of the compulsory course had switched completely to the online system for the first time. One way to measure the effectiveness of learning is to look at students' responses and reactions from their social presence and perceived learning. The purpose of this study was to gain insights into learners' social presence and perceived learning of online classrooms especially for CCU courses. Seventy (70) students of the English and Literature department were surveyed to identify helpful components and perceived challenges based on their online learning experiences in this course by using social presence scale questionnaires and online interviews. The results of the study illustrated the student's effort and expectation to the online classroom while most of them feel difficult and lack of activeness with online classrooms during the pandemic. Participants indicated that technical problems, lack of sense of community, time constraints, and the difficulties in understanding the objectives of the online courses as challenges.